Antifungal efficacy of crude aqueous weed extracts against pathogen of cocoa black pod rot / Nor Amerulah Nor Mohamad, Suhaida Salleh and Hamzah Abdul Aziz - Nor Mohamad, Nor Amerulah; Salleh, Suhaida; Abdul Aziz, Hamzah (Univeristi Teknologi MARA, Sabah, 2019)
Black pod rot is the most economically important disease of cocoa in Malaysia which is mainly caused by a highly polyphagous Phytophthora species, called Phytophthora palmivora. The fungus could attack all parts of the cocoa plant organs and caused various diseases at any growth stage from seedling until the mature stages, especially during raining season. The application of synthetic fungicides has been widely recommended to manage the disease but their repeated use had led to other problems such as environmental, human health and development of fungicide resistance issues. This study isolated and identified Phytopththora isolate from a cocoa pod sample based on micro-morphological characters. Besides, the present investigation was undertaken to screen for the antifungal potency of different weed extracts against the Phytophthora pathogen using poisoned food technique. The fungal isolate was successfully recovered from pod tissues of clone PBC123 on 20% tomato juice agar culture (20T). Only one out of ten weed extracts tested showed a significant in vitro inhibitory effect towards mycelial growth of Phytophthora isolate, which was aqueous crude leaf extract of Solanum torvum (42.68%). This study indicated that the potential of weed extracts in the management of Phytophthora diseases, and may offer more natural, effective and economical control methods.